Highly efficient and selective production of acrylic acid from 3-hydroxypropionic acid over acidic heterogeneous catalysts. (29th June 2018) - Li, Chao; Zhu, Qiangqiang; Cui, Ziheng; Wang, Bin; Fang, Yunming; Tan, Tianwei
Graphical abstract: Effect of acidity property on acrylic acid selectivity was established. Highlights: Highly efficient and selective production of acrylic acid was achieved. The presence of Brønsted acid sites results in the formation of acetic acid. Coke content increases with increasing amount of Brønsted acid sites. Abstract: The process for dehydration of 3-hydroxypropionic acid to produce acrylic acid was investigated over solid acid catalysts containing HY, ZSM-5, Beta, MCM-41 and silica gel. These catalysts were comprehensively characterized by techniques including XRD, nitrogen adsorption–desorption, NH3 -TPD, Pyridine-IR, TGA and 13 C CP MAS-NMR. Silica gel was found to show the highest acrylic acid selectivity of >99.0% at a complete 3-hydroxypropionic acid conversion. Results from NH3 -TPD and Pyridine-IR analyses reveal that the acidity has a significant effect on catalytic performance. The selective conversion of 3-hydroxypropionic acid to acrylic acid over silica gel can be ascribed to the weak and small amount of Lewis acid sites as well as the absence of Brønsted acid sites. Increasing Brønsted acid sites for HY, ZSM-5, Beta and MCM-41 resulted in low acrylic acid selectivities due to increasing of acetic acid formation. TG and 13 C CP MAS-NMR results further indicate that the presence of Brønsted acid sites favors the formation of coke. And the coke deposited on these catalysts has a primarily aromatic nature. Stability test indicates the silica gel catalyst exhibits an excellent stability for 200 h.